Negotiating the use of female-initiated HIV prevention methods in a context of gender-based violence: the narrative of rape. Issue 6 (2nd June 2016) - Hartmann, Miriam; Montgomery, Elizabeth; Stadler, Jonathan; Laborde, Nicole; Magazi, Busisiwe; Mathebula, Florence; van der Straten, Ariane
Abstract: Female-initiated methods of HIV prevention are needed to address barriers to HIV prevention rooted in gender inequalities. Understanding the sociocultural context of pre-exposure prophylaxis (PrEP) trials, including gender-based violence, is thus critical. MTN-003C (VOICE-C), a qualitative sub-study of the larger MTN-003 (VOICE) trial, examined sociocultural barriers and facilitators to PrEP amongst women in Johannesburg. We conducted focus-group discussions, in-depth interviews and ethnographic interviews with 102 trial participants, 22 male partners, 17 community advisory board members and 23 community stakeholders. We analysed how discussions of rape are emblematic of the gendered context in which HIV risk occurs. Rape emerged spontaneously in half of discussions with community advisory board members, two-thirds with stakeholders and among one-fifth of interviews/discussions with trial participants. Rape was used to reframe HIV risk as external to women's or partner's behaviour and to justify the importance of PrEP. Our research illustrates how women, in contexts of high levels of sexual violence, may use existing gender inequalities to negotiate PrEP use. This suggests that future interventions should simultaneously address harmful gender attitudes, as well as equip women with alternative means to negotiate product use, in order to more effectively empower women to protect themselves from HIV.